Analysis and Experimental Investigation of Vibration Characteristics of Rotary Platform of Hydraulic Excavator under Complex Working Conditions - Tinghao Li; Fuxiu Liu; Zhaojun Li; Mingjin Lu; Qiulu He (Shock and Vibration)
The rotary platform is the load-bearing substrate of a hydraulic excavator. The dynamic characteristics of the rotary platform directly affect the reliability and safety of the whole machine of a hydraulic excavator. In this work, the characteristics of the main external excitations acting on the hydraulic excavator such as the engine excitation, pressure pulsation excitation of the piston pump, inertial excitation of the working device, and road excitation are analyzed. The vibration transmission paths under the action of external excitations are ascertained. A vibration test method for the rotary platform of the hydraulic excavator is proposed. The vibration characteristics of the rotary platform under complex working conditions are researched, and the internal relationships between the vibration characteristics of the rotary platform and the engine excitation, pressure pulsation excitation of the piston pump, and road excitation are analyzed experimentally. The results show that the rotary platform is subjected to different excitations when it is under different working conditions. Moreover, the internal relationships between the dynamic characteristics of the rotary platform and the external excitation characteristics can be discovered by analyzing the vibration signals of the rotary platform, and the dynamic characteristics of the whole machine of the hydraulic excavator can be deeply studied based on the vibration characteristics of the rotary platform.